2021
DOI: 10.3389/fnagi.2021.742632
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence in Traumatic Brain Injury: Evidence and Perspectives

Abstract: Mild traumatic brain injury (mTBI) can lead to long-term neurological dysfunction and increase one's risk of neurodegenerative disease. Several repercussions of mTBI have been identified and well-studied, including neuroinflammation, gliosis, microgliosis, excitotoxicity, and proteinopathy – however the pathophysiological mechanisms activating these pathways after mTBI remains controversial and unclear. Emerging research suggests DNA damage-induced cellular senescence as a possible driver of mTBI-related sequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 105 publications
4
10
0
Order By: Relevance
“…The complex interrelationships among cellular senescence, neuroinflammation, and mitochondrial dysfunction in brain injury suggest approaches targeting neuroinflammation and mitochondrial might help attenuate cellular senescence [48]. In line with the previous study [48], rCHI induced neuronal senescence in the cortex, which was alleviated by PBM therapy. According to previous studies, persistent inflammation could accelerate the senescence process of neurons and other types of cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The complex interrelationships among cellular senescence, neuroinflammation, and mitochondrial dysfunction in brain injury suggest approaches targeting neuroinflammation and mitochondrial might help attenuate cellular senescence [48]. In line with the previous study [48], rCHI induced neuronal senescence in the cortex, which was alleviated by PBM therapy. According to previous studies, persistent inflammation could accelerate the senescence process of neurons and other types of cells.…”
Section: Discussionsupporting
confidence: 78%
“…Growing evidence suggests the existence of cellular senescence in traumatic brain injury [47]. The complex interrelationships among cellular senescence, neuroinflammation, and mitochondrial dysfunction in brain injury suggest approaches targeting neuroinflammation and mitochondrial might help attenuate cellular senescence [48]. In line with the previous study [48], rCHI induced neuronal senescence in the cortex, which was alleviated by PBM therapy.…”
Section: Discussionsupporting
confidence: 67%
“…It is characterized by proliferative arrest, secretory phenotype, macromolecular damage, and alternation in metabolism [36,37]. Several studies suggested that DNA damage-induced cellular senescence was a possible driver of TBI-associated sequelae such as cognitive impairment [38][39][40]. Among the common DEGs, several genes might play a role in the response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammatory mechanisms contribute to clear the injured brain and spinal cord of damage and to foster tissue regenerative mechanisms, especially remyelination. The consequences of TBI and SCI, however, include cell senescence ( 12 ), that may contribute to secondary injury. While this may be the substrate for neurodegenerative mechanisms secondary to repeated head concussions, this may also explain why the severity of long-term consequences after TBI or SCI is increased in elderly ( 10 , 12 ).…”
Section: Traumatic Brain and Spinal Cord Injuries And Neuroinflammationmentioning
confidence: 99%
“…The consequences of TBI and SCI, however, include cell senescence ( 12 ), that may contribute to secondary injury. While this may be the substrate for neurodegenerative mechanisms secondary to repeated head concussions, this may also explain why the severity of long-term consequences after TBI or SCI is increased in elderly ( 10 , 12 ).…”
Section: Traumatic Brain and Spinal Cord Injuries And Neuroinflammationmentioning
confidence: 99%